Towards a better way to evaluate internet usage - Haghighi B.T.; Othman M.; Hashim F.H. (2023)
Excessive usage of the Internet is known to cause many physical and mental problems which could eventually lead to Internet Addiction (IA). Knowing when to stop and recognizing the symptoms of problematic use is crucial in promoting a healthy use of the Internet. The purpose of this study is to develop an evaluation model that can be used to evaluate and analyze the usage of the Internet, and users' dependency level on the Internet. This study is divided into 2 major tasks: the first is focused on a review of several existing software applications which can track and trace online activities. Based on this review, an adapted model which evaluates Internet usage is proposed. The second major task assesses the levels of usage: the levels of '1' to '5' respectively describe 'not dependent', 'sufficient use', 'mild dependence', 'excessive use' and 'extreme' Internet Addiction. This paper proposes an evaluation model which analyses and evaluates Internet usage by tracing users' online activities. The types of Internet usage is defined as 5 dependency levels by focusing on the symptoms of problematic usage. In conclusion, this study attempts to propose the way for Internet users to focus on their Internet usage strategy. It helps them identify when they need to stop using the Internet, as well as choose a healthier strategy when using the Internet. Hence, Internet users are able to ultimately prevent or control Internet Addiction disorder.